(untitled) (Research, Society and Development, 2022)
This study aims to identify and analyze how the Brazilian Silhouettes Scale for children has been used in scientific research since its publication. Source of data: an integrative literature review was carried out through an electronic search of articles in the databases Pubmed, Scopus, SciELO, and Google Scholar. The name of the instrument in Portuguese and its variants in English were used for the search. No temporal filter was applied, although it is known that this tool was developed by Kakeshita and his collaborators in 2009. Only original articles that used the instrument were included; duplicate articles, literature reviews, case reports, summaries of annals of events; and / or works that did not use the target tool of this study. Summary of the findings: 216 studies were identified, and, after exclusion criteria, 16 studies were analyzed. The use of this instrument was observed in children and adolescents between 5 and 19 years of age, to assess satisfaction and the perception of body size both by children and their guardians. Conclusion: It is concluded that this scale has been used in most studies to assess satisfaction with body image, however, not all studies have respected its validation for children aged 7 to 12 years.